Bioética y biopolítica: la discriminación a los habitantes de la calle drogodependientes por su pobreza (2019)
The bioethical dilemma related to life and the application of the right is presented in relation to the Dignity of the consumer of narcotics inhabitant of the street, that is, the doctoral research project tries to establish whether consumption dignifies the human being or degrades it. The present article of reflection that gives account of this dilemma tries to describe the notions of aporophobia, exclusion and marginalization and generalizing social prejudices towards this population to demonstrate the absence of biojustical and biopolitics as branches of bioethics in the Colombian law system. A relationship was found between the studied notions that perpetuate discrimination in society and the family. The main conclusion is that the legal system, due to its lack of conceptual unanimity, favors the growth of the scourge of drug addiction to the point of exclusion and marginalization that condition human Dignity to the material. The method used is the interpretative documentary and the sustained reflection, in the information analyzed in indexed documents and journals, with critical discourse analysis.